2021
DOI: 10.1177/03635465211027305
|View full text |Cite
|
Sign up to set email alerts
|

Controversy on the Association of the Critical Shoulder Angle and the Development of Degenerative Rotator Cuff Tears: Is There a True Association? A Meta-analytical Approach

Abstract: Background: The role of the critical shoulder angle (CSA) as a risk factor for rotator cuff tear (RCT) remains controversial. Studies on the association between the CSA and RCT show considerable differences in design, and this could be responsible for the variation in study results. Purpose: To (1) describe the reliability of CSA measurement and (2) evaluate the results of the studies reporting the association between the CSA and RCT using meta-analytical techniques to explore potential sources of variation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…These research data can provide scientific evidence for the clinical application of the CSA and confirm that a larger CSA is a risk factor for RCT. At present, the published literature is controversial regarding the relationship between hypertension and the risk of RCTs ( 13 , 32 ). There are few studies on the mechanism of the internal relationship between hypertension and RCTs, so additional clinical and basic research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…These research data can provide scientific evidence for the clinical application of the CSA and confirm that a larger CSA is a risk factor for RCT. At present, the published literature is controversial regarding the relationship between hypertension and the risk of RCTs ( 13 , 32 ). There are few studies on the mechanism of the internal relationship between hypertension and RCTs, so additional clinical and basic research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Garcia et al [ 11 ] reported that contrary to previous studies, the average CSA values correlated with RCTs, where CSAs > 38° (range: 35°–39°) seemed to be a consistent predictor of RCTs and indicated an increased risk of retear after surgical repair. However, a meta-analysis showed that while the CSA can be reliably measured, the difference in the CSA between cases and controls varied from very large to almost no difference, and it is difficult to understand the strength and association between the CSA and RCT with the current evidence [ 13 ]. In addition, Cerciello et al [ 29 ] confirmed no significant differences in CSA values between patients who had undergone shoulder replacement and experienced late cuff failure and those in whom the same procedure had been successful.…”
Section: Discussionmentioning
confidence: 99%
“…Gerber et al [ 12 ] found that patients with CSAs > 35° had a higher retear rate after repair than those with CSA < 33° after lateral acromioplasty. However, a recent meta-analysis showed that it was difficult to obtain an exact association between the CSA and degenerative rotator cuff tears [ 13 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Morphologische Besonderheiten des Schultergelenks, insbesondere die Form des Schulterdaches [34,35], ein vergrößerter kritischer Schulterwinkel (CSA) [24,34,36], ein hoher akromiohumeraler Index [34,35] sowie eine generelle Schulterinstabilität [2,26] sind weitere Faktoren, die das Risiko der Erkrankung erhöhen. Inwieweit sich die Veränderungen des Subakromialraumes bei gleichzeitiger beruflicher Belastung verstärken, konnte bislang jedoch nicht sicher bestimmt werden.…”
Section: Nicht Berufliche Risikofaktorenunclassified
“…Morphological features of the shoulder, particularly the shape of the acromion [34,35], an enlarged critical shoulder angle (CSA) [24,34,36], a high acromiohumeral index [34,35] as well as a general shoulder instability [2,26], are other factors that increase the risk of disease. The extent to which the changes to the subacromial space increase with work-related stress could not yet be determined with certainty.…”
Section: Non-work-related Risk Factorsmentioning
confidence: 99%